Thermodynamic properties of poly(2-[3-(6-tetralino)-3-methyl-1-cyclobutyl]-2-hydroxy ethyl methacrylate) and poly[2-(3-mesityl-3-methyl-1-cyclobutyl)-2-oxoethyl methacrylate) - Ilter, Zuelfiye; Kaya, Ismet; Ercan, Selami (Taylor & Francis Inc, 2007)
In this study, some thermodynamic properties of poly( 2-[3-(6-tetralino)-3-methyl-1-cyclobutyl]-2-hydroxy ethyl methacrylate) P (TMCBHEMA) and poly[2-(3-mesityl-3-methyl-1-cyclobutyl)- 2- oxoethyl methacrylate) P ( MCBOEMA) such as the adsorption enthalpy, Delta H-a, molar evaporation enthalpy, Delta H-v, the sorption enthalpy, Delta H-1(s), sorption free energy, Delta G(1)(s), sorption entropy, Delta S-1(s), the partial molar free energy, Delta G(1)(infinity), the partial molar heat of mixing, Delta(H) over bar (infinity)(1), at infinite dilution were determined for the interactions of PTMCBHEMA and PMCBOEMA with selected alcohols and alkanes by the inverse gas chromatography (IGC) method in the temperature range of 333 - 463 K. According to the specific retention volumes, V-g(0), the weight fraction activity coefficients of solute probes at infinite dilution, Omega(infinity)(1), and Flory-Huggins interaction parameters, chi(infinity)(12) between PTMCBHEMA and PMCBOEMA-solvents were determined in 433 - 463K and 443 - 463K, respectively. According to Omega(infinity)(1) and chi(infinity)(12), selected alcohols and alkanes were found to be non-solvent for PTMCBHEMA at 433 - 463 K, but the same solvents ( except for decane) were found to be solvent for PMCBOEMA at 443 - 463K. The glass transition temperature, T-g, of the PTMCBHEMA and PMCBOEMA found to be 380 and 383; 390 K and 388 K, by IGC and DSC techniques, respectively.
Keywords: poly (2-[3-(6-tetralino)-3-methyl-1-cyclobutyl]-2-hydroxy ethyl methacrylate) and poly [2-(3-mesityl-3-methyl-1-cyclobutyl)-2; oxoethyl methacrylate); inverse gas chromatography; polymer-solvent interactions